MEMBANGUN POLA KOMUNIKASI KELUARGA UNTUK MENINGKATKAN RESILIENSI ANAK PASCA BENCANA - Jusmiati Jusmiati (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
This paper aims to elaborate family communication patterns in increasing resilience of children after disasters. A number of studies have stated that children are the most vulnerable victims of mental disorders, and have unstable resilience after a disaster. However, the writings there still revolve around the importance of disaster mitigation education since, no one has touched on the importance of family communication patterns in increasing children's resilience. This paper addresses this problem through content analysis of a number of primary sources of books and journals. The results of this study indicate that there are two effective patterns of family communication to build and increase resilience of children after a disaster. First, pluralistic communication is characterized by children's independence in making decisions. Second, consensus communication, which is a pattern of communication that is built on the principle of openness between parents and children, but the final decision is still determined by parents. Both patterns are very effective in building self-confidence, empathy and responsibility which are the characteristics of a strong child.